Adnexal Torsion in the Third Trimester of Pregnancy: A Challenging Diagnosis - Tayyar, Ahter Tanay; Tayyar, Ahmet; Atakul, Tolga; Senturk, Mehmet Baki; Cundubey, Cevat Rifat; Tayyar, Mehmet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The incidence of adnexal torsion (AT) is reported 1 in 10000 births. AT is emergency condition in pregnancy, while the risk of late diagnosis is increased, in third trimester. Since it has been described as a severe complication after controlled ovarian hyper-stimulation for in vitro fertilization (IVF), it is more common in IVF pregnancies. This condition mainly occurs in the first trimester; it is rare during the late third trimester. Herein, we report a case of a 26-year-old woman, gravida 1, singleton pregnancy in the 30th week of gestation was presented to emergency department with 24-hour history of a stabbing pain because of AT. Removal of adnexa performed by laparotomy. The patient had labour pain and cervical dilatation at the 36th week of gestation and a healthy girl weighing 2,200 g was born by emergency caesarean section due to breech presentation.